2019
DOI: 10.1155/2019/9710208
|View full text |Cite
|
Sign up to set email alerts
|

MitoCLox: A Novel Mitochondria-Targeted Fluorescent Probe for Tracing Lipid Peroxidation

Abstract: Peroxidation of cardiolipin (CL) in the inner mitochondrial membrane plays a key role in the development of various pathologies and, probably, aging. The four fatty acid tails of CL are usually polyunsaturated, which makes CL particularly sensitive to peroxidation. Peroxidation of CL is involved in the initiation of apoptosis, as well as in some other important cellular signaling chains. However, the studies of CL peroxidation are strongly limited by the lack of methods for its tracing in living cells. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…The earlier findings demonstrated that CL (a) was selectively oxidized under conditions compatible to those of our experiments and (b) could be protected against oxidation by cationic mitochondria-targeted antioxidants [44][45][46]. We suggest that MitoCLox most likely preferably reports on the oxidation of CL, in agreement with results of molecular dynamic modeling that predicted a particular affinity of MitoCLox to CL [29]. Specifically, the application of MitoCLox revealed that the oxidation of lipids took place immediately after addition of hydrogen peroxide and preceded the drop in MMP.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The earlier findings demonstrated that CL (a) was selectively oxidized under conditions compatible to those of our experiments and (b) could be protected against oxidation by cationic mitochondria-targeted antioxidants [44][45][46]. We suggest that MitoCLox most likely preferably reports on the oxidation of CL, in agreement with results of molecular dynamic modeling that predicted a particular affinity of MitoCLox to CL [29]. Specifically, the application of MitoCLox revealed that the oxidation of lipids took place immediately after addition of hydrogen peroxide and preceded the drop in MMP.…”
Section: Discussionsupporting
confidence: 91%
“…In all tested cases, MitoCLox was reliable in reporting LPO. The data obtained are fully consistent with the behavior of MitoCLox in the model liposome system [29].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations